Flexing the Flux: Re-Appropriating Muizenberg Beachfront as a response to contextual dynamism - Du Plessis, Michal (School of Architecture, Planning and Geomatics, 2021)
The study took place in order to gain an intuitive understanding of the physics that govern the movement of beach sand, and thereby, the formation of sand dunes. The experiment included placing a series of objects on a stretch of beach in Cape Town, and were observed over five days. The forms chosen represent the impact of man on the beach - specifically the physical alterations that man makes to this landscape typology. The presence of objects on the beach in turn, has visible impacts on the manner in which sand is transported and settled by meteorological components. These resultant 9dis0configuration of the surrounding landscape was documented in detail and alludes towards how the endeavours of mankind impact the nature of coastal landscapes. The study acts as an entry point into contemplating how responsive design approaches may apply to beachfront landscapes. The process is thus used as a catalytic guide for the dissertation that follows.